Islamic Bank Performance Assessment Using SATF Value - Rizal, Andi Muhammad (LPPM ISNJ Bengkalis, 2024)
This study aims to evaluate the performance of Islamic banks based on the shidiq, amanah, tabligh, and fathona (SATF value) approach. The type of research is descriptive quantitative using secondary data. The research population is all Islamic Commercial Banks (ICB) operating in Indonesia for 2018-2022. The sampling technique uses saturated samples. The data combines ICB annual financial reports issued by the Financial Services Authority (FSA) and literature studies. The data analysis technique uses simple additive weighting (SAW). The research results show that Shidiq's performance shows high public confidence in Islamic bank savings products. Amanah's performance shows that the distribution of financing and carrying out responsibilities to bring benefits still need to be higher. Tabligh's performance shows that the level of Islamic compliance carried out by banking operations is Islamic. Fathona's performance shows that Islamic banking still needs to be optimal in increasing human resources (HR) capability or quality. Overall, the results of evaluating the performance of Islamic banking in Indonesia using the SATF value model during 2018-2022 are entirely satisfactory, with the SATF performance value increasing from year to year. The results of this research can be a reference for future research and provide valuable guidance for maintaining and improving Islamic banking performance while actively correcting any identified weaknesses or deficiencies.